2017
DOI: 10.1111/sjop.12387
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of personality with integration and confrontation in internal dialogues

Abstract: Interest in confrontational and integrative internal dialogues (IDs) has been growing, as they perform numerous important functions. This study aimed to identify the personality-related determinants of integration and confrontation processes in ID that simulates social relationships. The test group comprised 125 students (62 men). Participants were given a description of a fictional problem facing a young married couple and they were to imagine a dialogue between the characters. Additionally three instruments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In previous studies (Puchalska‐Wasyl, ,, , ), the correlation between the indices of general integration (INT) and general confrontation (CONF) was non‐significant and close to zero. Similar results were obtained in the current study, in both the experimental (see Table ) and control (see Table ) groups.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…In previous studies (Puchalska‐Wasyl, ,, , ), the correlation between the indices of general integration (INT) and general confrontation (CONF) was non‐significant and close to zero. Similar results were obtained in the current study, in both the experimental (see Table ) and control (see Table ) groups.…”
Section: Methodsmentioning
confidence: 77%
“…Several studies show that general integration and general confrontation as defined in the two‐dimensional model of ID are not correlated with each other (Puchalska‐Wasyl, ,, , ), thereby supporting their theoretically postulated independence. At the same time, it should be emphasized that the integrative and confrontational attitudes of the ID author and his/her interlocutor can be related, reflecting different patterns of integrative and confrontational characteristics of IDs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that Faithful Friend and Ambivalent Parent are two types of internal interlocutors characteristic of integrative IDs (Puchalska‐Wasyl, ). Another study found that high openness, conscientiousness and agreeableness, combined with low neuroticism and anxious or avoidant attachments, are associated with higher integrative attitudes in both parties in the ID (Puchalska‐Wasyl, ). Finally, one study using canonical correlation analysis has shown that the greater the similarity between ID parties the stronger the author's and interlocutor's integrative attitudes, and the weaker the author's confrontational attitude.…”
mentioning
confidence: 99%
“…In light of the two‐dimensional model of ID (Puchalska‐Wasyl, , , ) which is adopted in this paper, general integration depends on integrative attitudes of both parties. Therefore, two additional hypotheses, which are in fact supplementary to the H2, were posed:
H2a.
…”
mentioning
confidence: 99%